2000
DOI: 10.1037/0022-006x.68.4.670
|View full text |Cite
|
Sign up to set email alerts
|

Community violence exposure and children's social adjustment in the school peer group: The mediating roles of emotion regulation and social cognition.

Abstract: This study reports a cross-sectional investigation of the relation between community violence exposure and peer group social maladjustment in 285 inner-city children in Grades 4-6 (mean age = 10.3 years). Children completed an inventory assessing exposure to community violence through witnessing and through direct victimization. A peer nomination inventory was then administered to assess social adjustment with peers (aggression, peer rejection, and bullying by peers). In addition, social-cognitive biases and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
399
2
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(433 citation statements)
references
References 51 publications
27
399
2
5
Order By: Relevance
“…However, it has been suggested that the correlates, consequences, and mechanisms of influence related to direct experiences (i.e., violence victimization) and observation of violence (i.e., witnessing violence) may differ significantly (Schwartz & Proctor, 2000). The potential impact of the experience of violence victimization on moral disengagement is unclear.…”
Section: Psychopathy and Moral Disengagementmentioning
confidence: 99%
“…However, it has been suggested that the correlates, consequences, and mechanisms of influence related to direct experiences (i.e., violence victimization) and observation of violence (i.e., witnessing violence) may differ significantly (Schwartz & Proctor, 2000). The potential impact of the experience of violence victimization on moral disengagement is unclear.…”
Section: Psychopathy and Moral Disengagementmentioning
confidence: 99%
“…The risk factors for aggressive behavior in childhood and adolescence are legion and include, among others: exposure to violence and aggression in the community (i.e., witnessing or being victimized by aggressive acts; Guerra et al 2003;Schwartz and Proctor 2000), in the family (e.g., viewing spousal abuse or receiving harsh physical discipline; Boxer et al (in press);McCloskey et al 1995), and in schools and peer groups (e.g., victimization by physically or relationally aggressive acts, membership in antisocial peer groups; Boxer et al 2003;Espelage et al 2003). Additional identified risk factors include academic difficulties (e.g., low intelligence, poor achievement, learning disability; Huesmann et al 1987;Stipek 1998); psychopathic tendencies or callousness-unemotionality (e.g., shallow affect, lack of concern for others; Frick et al 2003); and psychopathology or related emotional problems (e.g., depression, psychotic symptoms; Boxer 2007; Knox et al 2000).…”
mentioning
confidence: 99%
“…Such surveys have the potential to produce high-quality statistics, since they use interviewers who are trained specifically for that purpose and who are well equipped to deal with this sensitive topic" (United Nations 2013, 6). 9 See Durrant et al (1994) and Schwartz and Proctor (2000). 10 Seventy-one percent of rural parents and 55 percent of urban parents reported flogging as the most frequent response to perceived misbehaviour in their children.…”
Section: Intimate Partner and Family-related Homicidementioning
confidence: 99%